2019
DOI: 10.17059/2019-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Europeans Towards Green Products

Abstract: Currently, green production is becoming more important than ever before. Reasons are obvious without being specifi cally mentioned. Policy makers support various tools to encourage individuals and entities of using green products. Green public procurement (GPP) is a tool intended to support the achievement of environmental goals through the green purchasing. However, there is still scope for better use of GPP. What do policy makers need to know to propose an effi cient intervention to stimulate the use of gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The second most frequent keyword is GPP. According to Malatinec (2019), GPP represents a mechanism intended to facilitate the attainment of environmental objectives via green purchasing. Sustainable public procurement (SPP) ranks as the fourth most frequent keyword.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…The second most frequent keyword is GPP. According to Malatinec (2019), GPP represents a mechanism intended to facilitate the attainment of environmental objectives via green purchasing. Sustainable public procurement (SPP) ranks as the fourth most frequent keyword.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…Romodina and Silin (2016) argue that SPP comprises a combination of practices, policies and laws intended to integrate economic, social and environmental risks into PP activities and decisions to maximise profitability across the whole product life cycle. Unlike SPP, GPP focuses mainly on the environmental Public procurement research dimension of sustainability and aims to facilitate the achievement of environmental goals via green purchasing (Cheng et al, 2018;Malatinec, 2019). GPP is also of significant value in countries and regions where it is extensively implemented, as it promotes resource sustainability for future generations, encourages the market to be more innovative in the development of environmentally-friendly products and services and lowers the overall costs of purchasing and disposing of products and services (Ngunjiri, 2019).…”
Section: Scholarly Production Main Journals and Prominent Authorsmentioning
confidence: 99%
“…Chiripuci et al (2022) found that European customers showed more interest in consuming organic products as a model of sustainable food consumption, which gives incentives for huge investments in organic food. Malatinec (2019) found that European customers had a positive attitude towards green products made by Western European countries firms. Statistics related to sustainable products support this direction towards sustainability aspects.…”
Section: Introductionmentioning
confidence: 98%